KEDUDUKAN FATWA MAHKAMAH AGUNG DALAM HUKUM TATA NEGARA INDONESIA - Noor, Fauz (Siyasyatuna | Jurnal Hukum Tata Negara, 2021)
The purpose of this study is to find out how the influence of a Supreme Court Fatwa in determining the law at the highest judicial level, what matters are related to the Judicial Power of the Supreme Court in relation to Constitutional Law in Indonesia. The research method used in this study is descriptive analytical. . That is to describe an exposure or describe a situation that appears or is happening at the present time that is developing. Then analyzed and found a hope and a solution. That the authority of the Constitutional Court in statutory regulations is very important to make a decision in reviewing and analyzing a statutory regulation that is not relevant to the situation in society. So that the Constitutional Court can act as a separator of a law that cannot be accepted by the public at large and actually creates order as a whole. The Constitutional Court is a judicial institution that specifically analyzes and decides on legislation.